FROM DEFERRED TAXES TO EARNINGS STABILITY: THE MODERATING IMPACT OF TAX PLANNING ON CORPORATE FINANCIAL PRACTICES - Agus Fuadi; Yusnia Devarianti; Dian Sulistyorini Wulandari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the effect of deferred tax expense on earnings management and the moderating role of tax planning in this relationship. The research data were drawn from annual financial statements of non-financial companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, selected using purposive sampling. Panel data regression with a random effects approach was used, supported by Chow, Hausman, and Lagrange Multiplier tests. The results indicate that deferred tax expense has a significant positive impact on earnings management, suggesting that firms use the flexibility of deferred tax accounting to manipulate earnings. However, tax planning significantly moderates this relationship in a negative direction, indicating that firms with higher tax planning are less likely to rely on deferred tax expense as an earnings manipulation tool. These findings highlight the importance of monitoring tax accounting practices and ensuring transparency in tax planning to enhance financial reporting quality.